Peran Diplomasi Publik Amerika Serikat dalam Promosi Demokrasi dan Ham di Asia Tenggara: Studi Kasus Indonesia (2017-2020) - Mellynda Lasiuta; Triesanto Romulo Simanjuntak; Tunjung Wijanarka (Jurnal Kajian dan Penelitian Umum, 2026)
This study examines the public diplomacy of the United States toward Indonesia through the lens of Soft Power during the 2017–2020 period and its implications for Indonesia’s democratic environment. The study aims to analyze the United States’ public diplomacy approach through the Young Southeast Asian Leaders Initiative (YSEALI), Fulbright, and American Corner programs in supporting the strengthening of democratic values in Indonesia. This research employs a qualitative method with a descriptive approach through literature review, documentation, and interviews. The theoretical framework is based on Joseph S. Nye Jr.’s concept of Soft Power and Jan Melissen’s theory of public diplomacy. The findings indicate that the United States utilized non-coercive approaches through education, cultural exchanges, and people-to-people relations to build influence and foster long-term relationships in Indonesia. The YSEALI, Fulbright, and American Corner programs contributed to strengthening youth capacity, promoting academic exchanges, and expanding opportunities for dialogue and public openness. Nevertheless, the influence of this public diplomacy on Indonesian democracy remains indirect and longterm, as it continues to be shaped by domestic factors.